Synthesis of Delafossite Compound CuAlO2 by Hydrothermal Method and Its Characterization - IBNU ABDULLAH (NIM 10502008), GINANJAR
In this decade, transparent conductive oxides (TCOs) play an important role in the construction of thin film optoelectronic materials, such as flat panels, touch screens, and solar cells. The performance of the optoelectronic materials can be enhanced by using the p-type TCOs. Previous researches have proven that CuAlO2 (CAO) adopting the delafossite structure is an excellent candidate to be applied as p-type TCOs. In this research, CAO was synthesized and chareacterized. The synthesis was carried out by hydrothermal method. A variation was applied on the precursor type and the amount of mineralizer solution (NaOH) used. The advantage of using hydrothermal method instead of other methods is the relatively low temperature required. The crystal structure of the CAO was characterized by X-ray diffraction. The diffractogram was analyzed by Le Bail method using the Rietica software and was showed that its crystal structure is a rhombohedral-trigonal-structured oxide with the space group of R -3mH. Refinement of CAO structure showed the smaller Rp and Rwp values of the sample synthesized by using the larger amount of mineralizer. The DC-electroconductivity measurement as a function of temperature showed the correlation of the conductivity value and the amount of mineralizer used.